Sequencing-based large-scale genomics approaches with small numbers of isolated maize meiocytes - Dukowic-Schulze, Stefanie; Sundararajan, Anitha; Ramaraj, Thiruvarangan; Mudge, Joann; Chen, Changbin (Frontiers in Plant Science, 2014)
High-throughput sequencing has become the large-scale approach of choice, and enables the study of global gene expression and the distribution of specific chromatin marks and features. However, the limited availability of large amounts of purified cells made it very challenging to apply sequencing-based techniques in plant meiosis research in the past. In this paper, we describe a method to isolate meiocytes from maize anthers and detailed protocols to successfully perform RNA-seq, smRNA-seq, H3K4me3-ChIP-seq and DNA bisulfite conversion sequencing with 5,000 to 30,000 isolated maize male meiotic cells. These methods can be adjusted for other flowering plant species as well.